Brazil Low Carbon Case Study : Waste - World Bank (Washington, DC, 2013)
This report synthesis the findings for the waste sector of a broader study, the Brazil low carbon study, which was undertaken by the World Bank in its initiative to support Brazil's integrated effort towards reducing national and global emissions of Greenhouse Gases (GHG) while promoting long term development. The purpose of the present report is to assist in the preparation of public policy proposals regarding GHG emissions and the additional financial resources necessary. The main purpose of the scenarios is to provide an evaluation of the GHG emissions arising from the different approaches and methods for treating waste and to ensure that important environmental aspects are taken into account when key decisions are being made on the waste treatment technologies to be applied in Brazil. The World Bank and covers four key areas with large potential for low-carbon options: 1) Land Use, Land-Use Change, and Forestry (LULUCF), including deforestation; 2) transport systems; 3) energy production and use, particularly electricity, oil and gas and bio-fuels; and 4) solid and liquid urban waste.